Die belangrikheid van Kerkgeskiedenis en Kerkreg in die teologiese opleiding en vorming van studente - Botha, Schalk Jacobus (HTS teologiese studies, 2002)
The importance of Church History and Church Polity in the training and forming of theological studentsThe Nederduitsch Hervormde Kerk always has always been adamant that its ministers should be trained and formed in a theological faculty at a recognized university, where all the disciplines of theology are lectured. At a recent Church synod, the importance of Church History was questioned. In this paper the argument that Church History is not just important in the curriculum of theology, but indeed indispensable, is put forward. As Church Polity forms part of the Department of Church History at the Faculty of Theology (University of Pretoria), it is also included in the argument.